Analisis Sistem Antrian pada Bengkel Mobil Menggunakan Simulasi - Mirna Lusiani; Ryan Adiputra Irawan (Universitas Bunda Mulia, 2017)
In this globalization era we are encouraged to do something with effectively and easily, because the time becomes an important thing in supporting the public activities. Companies should give a good service for customer without reducing its quality with an efficient cost consideration. Because of it the company should is obliged to reduce the queue so the queue will be more effective than before and will increas the customer satisfaction. This study uses a simulation analysis to determine the queue in actual system. This simulation requires primary and secondary data (observations) on every stall in car repair shop. The next step after we know the problem from the queue simulation is creating an improvement simulation to change the process in queue, and reducing or increasing the existing stall on the actual system. The result obtained from data processing and analysis, it was found some problems that happen in the real queue system such as full capacity on some stall. Stall that needed to be improve are Spooring Stall, External Service Stall, and Washing Stall. And then the next step is doing some improvement to change the process from SBEK and SBIK to Spooring Stall into Spooring Stall to SBEK and SBIK. The second improvement is adding SBE Stall and Spooring Stall by reducing 2 SBI Stall.The conclusion in this study are the increasing amount of the output, from first improvement it increases to 115 entities and from second improvement it increases to 143 entities. Then the total time of entities in the system decreased from 456.299,47 second into 310.597,57 second dan 359.925,65 second for each improvement.Keywords: Queue, Simulation, Operations research